Sie sind auf Seite 1von 3

ROTATIONAL CONICS

Given that:

Therefore, x = r cosθ and y = r sinθ

= r cos(θ-α) and = r sin(θ-α)

Using the General Addition Formulas1, 2, we have:

= x cosα + y sinα and x= cosα - sinα Rotation Transformation

= y cosα – x sinα y= sinα + cosα Equations

To get the angle of rotation of the plane in which the xy coefficient disappears, we equate the
coefficients of the transformed general equation to zero. We get3:

cot2α = A-C

Almira xD
To know the graph of the tranformed equation beforehand, we make use of the discriminant.
Take note that4:
2
- 4Ā = B2 - 4AC
And so,

If Ā > 0, then it is an ellipse, with B2 – 4AC < 0

Ā = 0, either Ā=0 or =0, then it is a parabola, with B2 – 4AC = 0

Ā < 0, then it is a hyperbola, with B2 – 4AC > 0

PROVING
1
= r cos(θ-α) = r sin(θ-α)

= r (cosθcosα + sinθsinα) = r (sinθcosα - cosθsinα)


= (r cosθ)(cosα) + (sinθ)(r sinα) = (r sinθ)(cosα) – (r cosθ)(sinα)
= x cosα + y sinα = y cosα – x sinα

2
x = r cosθ y = r sinθ

= r ( (cosα)(cos(θ-α)) - (sinα)(sin(θ-α)) ) = r ( (sinα)(cos(θ-α)) + (cosα)(sin(θ-α)) )


= (r (cos(θ-α)))(cosα) – (r (sin(θ-α)))(sinα) = (r (cos(θ-α)))(sinα) + (r (sin(θ-α)))(cosα)

= cosα - sinα = sinα + cosα

3
Ax2 = Acos2α 2
– 2Asinαcosα + Asin2α 2
0 = B(cos2α - sin2α) + (C-A)(2sinαcosα)
2 2
Bxy=Bsinαcosα( - )+ B(cos2α-sin2α) = Bcos2α + (C-A)(sin2α)

Cy2 = Csin2α 2
+ 2Csinαcosα + Ccos2α 2
Bcos2α = (A-C)(sin2α)
cos2α/sin2α = (A-C)/B
cot2α = (A-C)/B

Almira xD
4
From the transformation of general equation (above),
Ā = Acos2α + Bsinαcosα + Csin2 α = Asin2α - Bsinαcosα + Ccos2α
= B(cos2α - sin2α) + (C-A)(2sinαcosα)

Then, B2-4AC 2
- 4Ā

(B(cos2α - sin2α) + (C-A)(2sinαcosα))2 – 4(Acos2α + Bsinαcosα + Csin2α)


(Asin2α - Bsinαcosα + Ccos2α)

B2cos4α -2B2cos2αsin2α + B2sin4α +4(BC-AB)(sinαcos3α)


+4(AB-BC)(sin3αcosα) + 4C2sin2αcos2α -8ACsin2αcos2α +4A2sin2αcos2α
-4A2sin2 αcos2α +24B2sin2αcos2α -4C2sin2αcos2α -4AC(sin4α+cos4α)
-4(BC-AB)(sinαcos3α) -4(AB-BC)(sin3αcosα)

B2cos4α + B2sin4α -8ACsin2αcos2α +2B2sin2 αcos2α -4AC(sin4 α+cos4α)

B2(cos4α+sin4α+2sin2αcos2α) – 4AC(2sin2αcos2α+ cos4α+sin4α)

(B2-4AC)(cos2α+sin2α)2

(B2-4AC)(1)2
≡ B2-4AC

Almira xD